Immersion infection of germ-free zebrafish with Listeria monocytogenes induces transient expression of innate immune response genes - Shan, Ying; Fang, Chun; Cheng, Changyong; Wang, Yong; Peng, Jinrong; Fang, Weihuan (Frontiers in Microbiology, 2015)
Zebrafish, Denio rerio, could be an alternative to other classic animal models for human infectious diseases to examine the processes of microbial infections and host-pathogen interactions in vivo because of their small body dimension but large clutch size. We established germ-free zebrafish infection models of Listeria monocytogenes through different routes of infection: oral immersion and injection via yolk sac, brain ventricle and blood island. Immersion of zebrafish larva even with 1010CFU/mL L. monocytogenes EGDe strain in egg water was unable to cause mortality, but GFP-expressing bacteria in the gut lumen could be observed in frozen sections. Several selected maker genes of the innate immune system, including cyp1a, irg1l, il1b and mmp9, were significantly induced by oral immersion not only with strain EGDe, but also with strain M7 and L. innocua, though to a lesser degree (P < 0.01). Such induction appears to be transient with peak at 48 h post-infection, but returned to basal level at 72 h post-infection. Of the three injection routes, mortality after infection by yolk sac was 80% in early stage of infection. Few eggs could survive and hatch. Injection into zebrafish embryos via brain ventricle or blood island led to progressive lethal infection. L. mocytogenes EGDe showed steady replication in the fish embryos and was far more pathogenic than strain M7, which is consistent with findings in the murine model. We conclude that zebrafish could serve as susceptible and microscopically visible infection models for L. monocytogenes via different routes and could be applied to further studies on the interactions between bacterial virulence factors and host immune responses.